2005
DOI: 10.1002/biof.5520250109
|View full text |Cite
|
Sign up to set email alerts
|

Life‐long supplementation with a low dosage of coenzyme Q10 in the rat: Effects on antioxidant status and DNA damage

Abstract: Life-long low-dosage supplementation of coenzyme Q(10) (CoQ(10)) is studied in relation to the antioxidant status and DNA damage. Thirty-two male rats were assigned into two experimental groups differing in the supplementation or not with 0.7 mg/kg/day of CoQ(10). Eight rats per group were killed at 6 and 24 months. Plasma retinol, alpha-tocopherol, coenzyme Q, total antioxidant capacity and fatty acids were analysed. DNA strand breaks were studied in peripheral blood lymphocytes. Aging and supplementation led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 58 publications
1
20
0
1
Order By: Relevance
“…It has been reported that CoQ supplementation suppressed PC levels in mice (Wadsworth et al 2008) which coincides with our results because we observed a significant decrease in PC levels after consumption of Med+CoQ diet compared with either the non-supplemented Med diet or the SFA-enriched diet. In addition, low oxLDL and LPO levels obtained after the intake of the Med+CoQ compared with the other diets is indicative of lower oxidative damage due to an antioxidant environment provided by CoQ supplementation (Quiles et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CoQ supplementation suppressed PC levels in mice (Wadsworth et al 2008) which coincides with our results because we observed a significant decrease in PC levels after consumption of Med+CoQ diet compared with either the non-supplemented Med diet or the SFA-enriched diet. In addition, low oxLDL and LPO levels obtained after the intake of the Med+CoQ compared with the other diets is indicative of lower oxidative damage due to an antioxidant environment provided by CoQ supplementation (Quiles et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In many tissues, ubiquinol-10 biosynthesis and levels decrease with age, suggesting that ubiquinol-10 may have possible anti-aging effects (1). Furthermore, nuclear DNA (nDNA) damage in rat blood lymphocytes, mitochondrial DNA (mtDNA) damage in rat heart, and mitochondria deletion and age-related molecular changes in rat brain mitochondria were suppressed by ubiquinone-10 (39,45,46). These findings may support the possibility that ubiquinol-10 has anti-aging effects, because ubiquinone-10 is readily reduced to ubiquinol-10 after dietary uptake (33,63) and a ratio of ubiquinol-10 to total CoQ10 of more than 85% is maintained in the plasma (40,70).…”
Section: Introductionmentioning
confidence: 99%
“…CoQ plays a crucial role in the generation of cellular energy, enhances the immune system, and acts as a free radical scavenger with antioxidant properties (Quiles et al 2005). Aging, poor eating habits, and stress affects the organism's ability to provide adequate amounts of CoQ.…”
Section: Introductionmentioning
confidence: 99%